Design of Gallium Phosphate Surface Acoustic Wave Resonator Using Finite Element Method - Mousavi, Sayed Alireza (2009)
The research into Surface Acoustic Wave (SAW) devices began in the early 1970s and led to the development of high performance, small size, rigorous and high reproducibility devices. SAW devices have been recognized for their versatility and efficiency in controlling and processing of electrical signals. Much research has now been done on the application of such devices to consumer electronic, communication systems and process function, such as delay lines, filters, resonator, and pulse compressors. The use of novel material, such as Gallium phosphate (GaPO4), extends the operating temperature of the SAW elements. In this thesis SAW devices based on this new material, operating at resonance frequency of 433.92 MHz been studied for passive wireless application. The SAW devices consist of interdigital transducer (IDT) with 1.4 μm finger gap ratio of 1:1 of platinum and under-layer of chromium metallization. A modeling using lumped equivalent circuit (LEC) of the device and finite element modeling (FEM) was done. The frequency responses of device were simulated by Sparameter and impedance. The impedance was used to study the mass loading effect of the Platinum electrodes of the SAW devices. The analysis of the result shows that the mass loading affects the resonant frequency of the SAW device. Furthermore, the results show that FEM approach is more precise than LEC for design and simulation of SAW resonator.